The relationship between impacted mandibular third molar and mandibular canal on orthopantomogram – a retrospective study - Mustafa, Naziyah Shaban; AbdulQadir, Omar Abdul Jabbar; Kashmoola, Sayfaldeen; Che Ku Abdullim, Engku Musfirah; Che Mohd Hashim, Nur Izzah (Greenfort International Publisher, 2024)
Background: Surgical removal of the impacted lower third molar teeth require thorough investigations and assessment, one of these very important investigations is orthopantomogram (OPG) which is the primary assessment method, to determine the relationship between impacted mandibular third molar and mandibular canal. The study aims to determine the relationship between impacted mandibular third molar and mandibular canal on orthopantomogram. Materials and methods: A retrospective of 300 OPGs out of 947 OPG were selected using simple random sampling method. Rood’s criteria was used in assessing the relationship between the apex of the roots and upper border of the inferior alveolar canal. Statistical analysis was performed to assess the relationship between the canal and the impacted lower third molar in relation to the age ,gender and type of impaction.Results: From 300 OPG, 473 impacted teeth were identified, the relation showed, the highest percentage was superimposed with 47.3%, followed by close contact (35.7%), and only 21.7% of the impacted teeth examined has distance between the roots and the upper border of mandibular canal.Conclussion:Mesioangular impaction has higher percentage of superimposition with the mandibular canal with the higher percentage of female58% to male42% ratio.